The improvement of sensitivity in lead and cadmium determinations using flame atomic absorption spectrometry - Yaman, M (Academic Press Inc Elsevier Science, 2005)
Various designs of quartz tubes of the slotted tube atom trap were examined to improve the sensitivity of flame atomic absorption spectrophotometry. The studied designs include the diameter length and the length of the upper slot of quartz tubes. Tubes having a diameter of 5 and 6 mm and an upper slot length of 2.3 cm produce the best sensitivity-as high as 6- and 10-fold enhancement for lead (Pb) and cadmium (Cd), respectively. The limits of quantitation were found to be 35 and 4 ng ml(-1) for Pb and Cd, respectively, by the optimized method. The achieved technique was applied to determine the concentrations of Ph and Cd in cancerous (malign) and noncancerous (adenoma) human thyroid tissues. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: STAT; sensitivity improvement; flame atomic absorption spectrometry; lead; cadmium; thyroid